THE BENEFITS OF LEARNING OUTCOMES STUDENTS PRESERVING FOOD AT READINESS PRODUCTS ENTREPRENEURSHIP PRESERVED FOODS - Wiji Nurcahyani; Ellis Endang Nikmawati; Rita Patriasih (Universitas Pendidikan Indonesia (UPI), 2013)
The background of research is the result of the practice preserving food that has not been used optimally as entrepreneurial opportunities by students. The purpose of this study to know the benefits of learning outcomes in readiness entrepreneurship food preservation products at food and culinary education study program 2010. The method used is descriptive and the sample are purposive by 48 respondents. Research data collection using the closed questionnaire. The results showed the benefits of learning outcomes in food preservation entrepreneurship student readiness preserved food products associated with mastery and understanding of the material to be useful to the criteria with an average percentage of 64%, the accuracy and precision in the use of food additives (BTM), packaging and labeling attitudes and knowledge related to entrepreneurship preserved food products are quite beneficial to the criteria with an average percentage of 60%, in the preparation of a mature business planning related to readiness for entrepreneurship motives and purposes are beneficial to the criteria with an average percentage of 65% , the failure to address the students' skills in practice relating to physical readiness, attitudes and emotional criteria are useful in the average percentage of 64%, and the skills of students in practicing a variety of food preservation products that vary relating to preservation readiness skills are at useful criteria with an average percentage of 63%. Suggestions to food and culinary education study in order to maintain and develop the knowledge, attitudes and skills to be better prepared entrepreneurship preserved food products.